BECOMING A BODY WAYFARING: EDUCATION AND THE BODY IN TIM INGOLD'S THOUGHT - Pich, Santiago (2021)
The article deals with the place of the body and education in the thought of Scottish anthropologist Timothy Ingold. We present the main metatheoretical assumptions of the author, highlighting those that are central to our argumentation: the pairs nature-culture, body-mind and animality-humanity. Ingold's thought is a wager on human education referenced in becoming, understood as a singular insertion in a tradition that is always situated on the plane of historicity and immanence, which does not have a pre-defined direction, but rather constitutes wandering, starting from a relationship of attention and perception of the world mediated by others who are already present in it. The body is conceived as a constitutive dimension of the human being, without which it is impossible to understand the way of being-with-others in the world. In it human potential is realized, and attention and perception are crucial. By problematizing the consequences of this thought for human education and body education, we found powerful conceptual tools to criticize the modern tradition of education, as well as to envision another way of conceiving human formation and body education, which are not understood as mere transmission of knowledge with which one operates logically, nor as the formation of a material body that should function in the best possible way, but conceived as the transmission of a singular form of perception and (re) creation of the world and as an instance of creating paths wayfaring, respectively.